Reflective Practice on Students' Experiences with the Use of Video Tutorial Procedure Text - Shelvia Ariesta Nabila; Koesomo Ratih (Kalam Al Gazali: Education and Islamic Studies Journal, 2025)
Reflective practice by involving students' experience in learning English using video tutorials with procedure text material helps teachers implement technology-based learning. Through reflective practice analysis, this article aims to explore and analyze students' reflective experiences when using video tutorials as learning media in writing procedure texts. In addition, this article will also discuss the effectiveness and engagement of students when learning using technology through video tutorials compared to conventional methods. As well as discussing the challenges faced and solutions when technology-based learning. This research uses a qualitative approach to understand students' experiences in using video tutorials to learn how to write procedure texts. The data used came from classroom observations, student interviews, and filling in google form. Student interviews were taken using voice recordings from cell phones. The analysis method consists of two main steps. First, analyze the completeness of the procedure test structure such as goals, ingredients/tools, and steps. The analysis was carried out using a score table to determine the value of each student who was complete and who was not. Second, the analysis of students' experience was carried out by taking a sample of student voices using the technique through filling out the gform, then the link was given to the teacher and distributed in the class grub through the English subject teacher. Then students fill out the gform questionnaire individually.